A simple quinolone Schiff-base containing CHEF based fluorescence 'turn-on' chemosensor for distinguishing Zn2+ and Hg2+ with high sensitivity, selectivity and reversibility. Issue 20 (11th May 2017) - Dong, Yuwei; Fan, Ruiqing; Chen, Wei; Wang, Ping; Yang, Yulin
Abstract : A new quinoline-based chemosensor was synthesized for the sensing of Zn 2+ and Hg 2+ . The degree of enhancement of the ICT and CHEF effects plays the key role to detect Zn 2+ and Hg 2+ with different fluorescence colors. Abstract : A new simple 'dual' chemosensorMQA (( E )-2-methoxy- N -((quinolin-2-yl)methylene)aniline) for distinguishing Zn 2+ and Hg 2+ has been designed, synthesized and characterized. The sensor showed excellent selectivity and sensitivity with a fluorescence enhancement to Zn 2+ /Hg 2+ over other commonly coexisting cations (such as Na +, Mg 2+, Al 3+, K +, Mn 2+, Fe 2+, Fe 3+, Co 2+, Ni 2+, Cu 2+, Ga 3+, Cd 2+, In 3+ and Pb 2+ ) in DMSO–H2 O solution (1/99 v/v), which was reversible with the addition of ethylenediaminetetraacetic acid (EDTA). The detection limit for Zn 2+ /Hg 2+ byMQA both reached the 10 −8 M level. The 1 : 1 ligand-to-metal coordination patterns of theMQA-Zn 2+ andMQA-Hg 2+ were calculated through a Job's plot and ESI-MS spectra, and were further confirmed by X-ray crystal structures of complexesMQA-Zn 2+ andMQA-Hg 2+ . This chemosensor can recognize similar metal ions by coherently utilizing intramolecular charge transfer (ICT) and different electronic affinities of various metal ions. DFT calculations have revealed that the energy gap between the HOMO and LUMO ofMQA has decreased upon coordination with Zn(ii )/Hg(ii ).